Avaliação e proposta de capacitação de profissionais médicos da Rede Pública de Urgência e Emergência em relação ao atendimento do escroto agudo - Jurado, Marcelo Mai (2021)
The acute scrotum is a urological emergency. Testicular torsion should be diagnosed as soon as possible and referred for surgical treatment within a maximum period of 12 hours in order to preserve the twisted testicle. Objectives: To assess whether doctors in the emergency services are prepared to make a diagnosis and referral for treatment in a timely manner; Based on the data obtained, propose training for working doctors and a new flow of care. Methodology: Exploratory, cross-sectional, qualitative and quantitative study with characteristics of action research through the application of a multiple choice questionnaire and open questions after presentation of a clinical case concept. Results: 83 physicians working in the health services of Sorocaba were evaluated. 24% of those evaluated had an average of correct answers for less than half of the questions. It was observed that the individuals who usually examine the patient with testicular complaints had a statistically higher mean score than those who did not examine (p <0.01), a higher mean was also observed among those who underwent medical residency, however, not significant (p=0.094). The individuals reported difficulties in referring patients for treatment, mainly related to regulatory system, lack of specialists and difficulties in transportation. Discussion: About ¼ of those evaluated had a low number of correct answers and may not be prepared for handling the acute scrotum cases. Examining the patient, having already had contact with a similar case in life or having undergone medical residency were positive predictive factors for a greater number of correct answers. Conclusion: It is necessary to train the physicians responsible for attending the emergency units, in addition to reviewing the flow of care for these patients, in order to increase the rate of testicular salvage in these cases